2019
DOI: 10.20961/carakatani.v34i1.27714
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Farmers' Entrepreneurial Behavior on Business Performance of PUAP Program in Pandawai Sub-district, East Sumba Regency

Abstract: Rural Agribusiness Development (<em>PUAP</em>) was a program for poverty alleviation among farmers through capital assistance with entrepreneurship training. This study were aimed to determine: (1) the effect of internal factors, <em>Gapoktan</em> dynamics and supporting factors of the <em>PUAP</em> program on farmers' entrepreneurial behaviors and (2) the effect of farmers' entrepreneurial behavior on the farmers' business performance whose received <em>PUAP</em>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The business performance was significantly influenced by the entrepreneurial behaviour. Ariesa (2013), Puspitasari et al, (2018) and Saragih et al, (2019) found on their studies that the entrepreneurial behaviour of smallholders significantly influenced the business performance. They argued that business performance could be improved through the vital role of entrepreneurial behaviour.…”
Section: Literatur Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The business performance was significantly influenced by the entrepreneurial behaviour. Ariesa (2013), Puspitasari et al, (2018) and Saragih et al, (2019) found on their studies that the entrepreneurial behaviour of smallholders significantly influenced the business performance. They argued that business performance could be improved through the vital role of entrepreneurial behaviour.…”
Section: Literatur Reviewmentioning
confidence: 98%
“…The relationship between entrepreneurial behaviour and business performance in general model adopted from Delmar (1996) was directly obtained without intermediary. The entrepreneurial behaviour had a direct and positive impact towards the business performance (Puspitasari et al, 2018;Saragih et al, 2019). The business ties were able to influence the entrepreneurial orientation and innovation performance (Urban, 2019;Zhang et al, 2020).…”
Section: The Effect Of Entrepreneurial Behaviour Of Pepper Farmer Tow...mentioning
confidence: 98%
“…This finding was in line with the one of [27] that the role of farmer groups is influenced by the management ability of the group and extension workers' resources. Meanwhile, [32] and [36] identified that the effectiveness of the group in achieving its objectives could be measured in the attainment of circumstances or physical or non-physical.…”
Section: The Role Of Farmer Groups In Application Of Integrated Farmi...mentioning
confidence: 99%